Effect of low radiation dose on the expression and location of aquaporins in rat submandibular gland - Araujo, M. V. T.; Spadella, M. A.; Chies, A. B.; Arruda, G.; Santos, T. de M. [UNESP]; Cavariani, M. M. [UNESP]; Domeniconi, R. F. [UNESP] (Churchill Livingstone, 2018)
Head and neck cancers are common in several regions of the world and the treatment usually includes radiotherapy. This treatment can generate adverse effects to the salivary flow, with a relationship between the dose and the damage caused. Salivary gland cells are highly permeable to water and therefore, they express aquaporins (AQPs). This study analyzed changes in the expression and location of these proteins and identified morphological changes induced by low radiation in rat submandibular gland. Female rats were divided into control and irradiated groups. Immunohistochemistry analysis allowed confirming the presence of AQP1 in the blood vessel endothelium. Intense and steady labelling granules were also observed in the cytoplasm of submandibular gland ductal cells. In addition, there was AQP5 positive labelling in ductal cells delimiting the lumen of intercalated duct, in the cytoplasm and membrane of acinar cells. Finally, the decrease of AQP labelling in irradiated animal glands validated their radiosensitivity. Thus, the decrease in AQP1 protein levels in the endothelium and AQP5 in gland ductal cells of irradiated animals may have hindered the removal of water from the lumen of ductal cells, inducing a delay in water absorption and triggering a slight lumen increase.
Keywords: Salivary glands; Irradiation; Water channels